THE BENEFIT OF THE PUBLIC POLICY FOR THE DIGITAL INCLUSION OF THE ELDERLY (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2020)
This article aims to demonstrate how technologies can impact and influence the life of the elderly. Digital information and communication technologies (TDCI), the use of smatphones, tablets and computers facilitated online communication, enabled consumption on national and cross-border lines, expanded access to public agencies through digital platforms and facilitated banking transactions. through apps. The growth of these media and information does not stop. Universal access for all, equal opportunities and social justice must be guaranteed. Thus, for a society to be digitally included, everyone must know the benefits and have access to information and communication technologies, including the elderly population. The adopted method was the analytical-deductive, making use of legal material, from books, scientific articles, laws and online sites that were analyzed in the elaboration of the research, aiming to bring to light the controversial questions and respective discussions of the subject, having as motto the digital inclusion of the elderly. Thus, a review of the national and international literature was conducted to verify what recent studies point to about digital inclusion, and how public policies have contributed to the insertion of older people in the technological environment